The influencing factors of gas adsorption behaviors in shale gas reservoirs - Lin, Xiaoying; Liu, Caijie; Wang, Zhirong (Frontiers in Earth Science, 2023)
The adsorption state is one of the main states for shale gas occurrence, and the gas adsorption behavior in shale directly affects shale gas content under reservoir conditions. This paper provides a comprehensive literature review on shale gas adsorption behavior and its affecting factors that have been developed in recent years. Influence factors of gas adsorption behavior are examined, including total organic carbon content (TOC), organic matter type, organic matter maturity, minerals and clay minerals, moisture content, pore characteristics and other characteristics of the shale itself. The characteristics of gas adsorption behavior under high temperature and pressure conditions showed that adsorption behaviors were difficult to describe by the Langmuir equation. This review indicates that shale contains higher organic matter content and organic matter maturity and has a higher adsorption capacity. The adsorption capacity with type III kerogen is higher than that for type II or type I. Clay minerals can provide free space for gas adsorption and promote adsorption. Normally, as the moisture content increased, adsorption capacity decreased. Micro pores provided a larger specific surface area for gas adsorption. As the temperature increased, the adsorption capacity decreased. As the pressure increased, shale adsorption characteristics showed two different behaviors as follows: one obeyed the Langmuir equation, and the other presented an inverted, U-shaped, single-peak distribution. However, there are some controversies surrounding adsorption, especially regarding the aspects of clay minerals, water content, pore characteristics, etc. The key is that the mechanism of adsorption in shale is unclear. There will be many new challenges in the field of shale gas adsorption research. Such challenges include studying the organic matter chemical structure, understanding the interaction between organic matter and clay minerals and how they affect adsorption, clarifying gas adsorption behavior changes, predicting favorable areas of adsorbed gas with the coupling of reservoir temperature and pressure, and building a better theory and model of shale gas adsorption.